The role of miR-29a in HIV-1 replication and latency - Giacomo Frattari; Lars Aagaard; Paul W. Denton (Elsevier, 2017)
The development of an effective HIV-1 eradication strategy relies upon a clear understanding of the cellular mechanisms involved in HIV-1 latency. Among such cellular processes, microRNA activities affect HIV-1 production by regulating viral transcripts as well as host cell HIV-1 dependency factors. miR-29a stands apart from other relevant microRNAs as a potential therapeutic target in HIV-1 eradication. In vitro experiments have shown that miR-29a binds to a sequence in the 3'UTR of viral transcripts and inhibits their expression. In vivo data revealed the existence of a cytokine-microRNA (i.e. IL-21/miR-29a) pathway that significantly impacts HIV-1 replication. Here we present and discuss evidence supporting the role of miR-29a in HIV-1 replication and latency. We also discuss potential clinical applications of miR-29a inhibitors and enhancers in HIV-1 eradication strategies.